Ancient African Kingdoms : A captivating guide to civilizations of ancient Africa such as the land of Punt, Carthage, the Kingdom of Aksum, the Mali Empire, and the Kingdom of Kush. - Captivating History (Oregon: Captivating History, 2020)
Africa is the continent where the first humans were born. They explored the vast land and produced the first tools. And although we migrated from that continent, we never completely abandoned it. From the beginning of time, humans lived and worked in Africa, leaving evidence of their existence in the sands of the Sahara desert and the valleys of the great rivers, such as the Nile and the Niger. Some of the earliest great civilizations were born there, and they give us an insight into the smaller kingdoms of ancient Africa. Egypt is the main source of knowledge of many neighboring kingdoms that were just as rich and developed. Unfortunately, they were forgotten in time, as other civilizations and kingdoms replaced them as the continent's power bases. Only recently are we rediscovering the might of the Kingdom of Aksum, the political prowess of Kush, and the richness of the mysterious Punt. The early medieval kingdoms of Ghana and Mali are still being researched due to their unique pre-Muslim culture and their own outlook on Islam. Because of the huge diversity that is the history of Africa, learning about it may be a bit of a challenge. Even though humanity started in that place, we somehow lost interest in it. And although the archaeology programs founded in the mid-20th century helped resolve this somewhat, we are still trying to eliminate the ignorance and racial prejudice of colonial times. Africa keeps many secrets, and they are there, ripe for the picking. The kingdoms discussed in this book serve as an inspiration to future generations to explore what lies below the African ground and behind its oral traditions.
Includes bibliographical references (pages 214-215).
Keywords: Civilization; Civilisation; civilization; Civilization; Africa -- History; Africa -- Civilization; Afrique -- Histoire; Africa; History